Comparative Life Cycle Assessment of Asphalt Mixtures Using Composite Admixtures of Lignin and Glass Fibers - Ahmed Khater (MDPI AG, 2021)
Lignin and glass fiber were used as additives to improve the quality of road pavements and minimize moisture damage and cracking at low temperatures on asphalt pavement, according to a previous laboratory study. The aim of this paper is to make a significant contribution to the environmental assessment of the construction of road pavements using four types of asphalt mixtures based on the life cycle assessment (LCA) methodology according to the requirements of ISO 14040, considering the impact of raw material extraction, asphalt mixture manufacturing, transportation, and wearing surface construction. The results of the environmental assessment showed that all studied asphalt mixtures do not offer any improvement in all impact categories, and three modified asphalt mixtures have a slight negative effect in all impact categories. The composite mixture has the highest negative effect of the studied three modified asphalt mixtures in all categories except in the marine aquatic ecotoxicity potential category and freshwater aquatic ecotoxicity potential category, where the lignin modified asphalt mixture has the highest negative effect in these two categories but has the best environmental impacts on most of other impact categories. Furthermore, the negative effect caused by composite asphalt mixtures is minimal and thus can be used to improve the overall performance of asphalt pavement.